Khulafa Al-Rasyidin (Dinamika Sosial Politik dan Dakwah Islam) - Susmihara, Susmihara (Fakultas Adab dan Humaniora UIN Alauddin, 2015)
The election of Abu Bakr as the Caliph is on the basis of democracy. Baiat generally performed better than the Muhajirin and Ansar. He managed to fight the apostates and the liar who claim to be prophet, so the transition is successfully passed by the Caliphs. Appointment of Umar ibn al-Khattab instead of Abu Bakar also complies with the constitution because through deliberation that does not use an authoritarian system. During his reign, Umar managed to bring the glory of Islam and set the state administration into an ideal shape. Usman ibn Affan elected as Khalifah based system acclamation. Attainment Usman in the lead and the softness of his heart without realizing opportunities influx of calumny at the end of his leadership that led to his killing. While accusations of nepotism addressed to Usman totally unwarranted and can be rejected. Ali ibn Abi Talib reigns at a difficult time in which the split occurs in the body of the people. Ijtihad difference in demanding justice for the murder Usman is the main cause of the civil war, not because of a power struggle.